Fetal Growth Restriction Caused by Sexual Transmission of Zika Virus in Mice - Uraki, Ryuta; Jurado, Kellie Ann; Hwang, Jesse; Szigeti-Buck, Klara; Horvath, Tamas L.; Iwasaki, Akiko; Fikrig, Erol (The Journal of infectious diseases, 2017)
Zika virus (ZIKV) can be transmitted by mosquito bite or sexual contact. Using mice that lack the type I interferon receptor, we examined sexual transmission of ZIKV. Electron microscopy analyses showed association of virions with developing sperm within testes as well as with mature sperm within epididymis. When ZIKV-infected male mice were mated with naive female mice, the weight of fetuses at embryonic day 18.5 was significantly reduced compared with the control group. Additionally, we found ocular deformities in a minority of the fetuses. These results suggest that ZIKV causes fetal abnormalities after female mating with an infected male.